KEKERASAN DALAM RUMAH TANGGA DARI KACAMATA PERAN BP4 (Harmoni, 2014)
Domestic Violence (domestic violence) is a universal case that led to the complex effects when compared with other forms of violence. Domestic violence is marital affairs, so that people still think of domestic violence as a private family matter. State institutions that are closest to the problems of marital affairs is Marriage Guidance and Preservation Board (BP4). Thus the problem of domestic violence should be a BP4 domains at the initial level. In fact, BP4, can not function well on the problem of domestic violence, especially in the City of Palembang due to several factors: the lack of understanding in BP4 officers about domestic violence, lack of support in term of government policy, there is no coordination between BP4 and Courts as well as the lack of infrastructure.
Keywords: Marriage; Domectic Violance; Regulation; Pernikahan; Kekerasan Dalam Rumah Tangga; Regulasi